2015
DOI: 10.1039/c5py00755k
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic- and heterotactic-specific radical polymerization of N-n-propylmethacrylamide complexed with alkali metal ions

Abstract: We investigated the radical polymerization of N-n-propylmethacrylamide (NNPMAAm) in the presence of alkali metal bis(trifluoromethanesulfonyl)imides (MNTf 2 ), in particular LiNTf 2 . The addition of MNTf 2 led to a significant improvement in the yield and molecular weight of the resulting poly(NNPMAAm)s. Furthermore, the solvent employed influenced stereospecificity in the presence of LiNTf 2 . The stoichiometry of the NNPMAAm-Li + complex appeared to be critical for determining the stereospecificity in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 85 publications
(226 reference statements)
3
27
0
Order By: Relevance
“…53,54 Indeed, in spectroscopic investigations of vinyl monomers and Li 1 salts, cation complexation has been detected using IR as well as 1 H and 13 C NMR spectroscopy. 55,56,[58][59][60] Based on similar evidence, it can be confirmed that these species are also formed in our study. As displayed in Figure 9, the C@O stretching peaks of MMA undergo shifts to lower wavenumbers following the addition of LiTf 2 N at monomer:salt ratios of 1:1 and 2:1.…”
Section: -68supporting
confidence: 89%
See 4 more Smart Citations
“…53,54 Indeed, in spectroscopic investigations of vinyl monomers and Li 1 salts, cation complexation has been detected using IR as well as 1 H and 13 C NMR spectroscopy. 55,56,[58][59][60] Based on similar evidence, it can be confirmed that these species are also formed in our study. As displayed in Figure 9, the C@O stretching peaks of MMA undergo shifts to lower wavenumbers following the addition of LiTf 2 N at monomer:salt ratios of 1:1 and 2:1.…”
Section: -68supporting
confidence: 89%
“…60,63,64 Likewise, the increase in the rate of polymerization of ACR and MACR monomers in the presence of alkai Tf 2 N salts was partly attributed to the decrease in the difference in the 13 C and 1 H NMR shifts of vinylidene carbon and H atoms that have been previously associated with favorable propagation kinetics. 58,59,65 The presence of these salts also affects the termination kinetics of these reactions, resulting in substantial increases in the radical concentrations of the reaction mixtures as determined by electron paramagnetic spectroscopy. 56,58,59 The mechanism of the reduction in the rate of termination in these reactions has been assigned to a variety of factors including radical stabilization and single electron-alkali metal interactions as well as electrostatic repulsion between complexed macroradicals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations